2017
DOI: 10.1109/tvcg.2016.2598430
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Photon Mapping for Interactive Global Illumination of Time-Varying Volumetric Data

Abstract: Abstract-We present a method for interactive global illumination of both static and time-varying volumetric data based on reduction of the overhead associated with re-computation of photon maps. Our method uses the identification of photon traces invariant to changes of visual parameters such as the transfer function (TF), or data changes between time-steps in a 4D volume. This lets us operate on a variant subset of the entire photon distribution. The amount of computation required in the two stages of the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…While this method allows real-time radiance reconstruction, the photon map should be regenerated every time the transfer function changes. To accelerate the photon map generation, Jönsson et al [24] identified photons invariant to changes of visual parameters (e.g., changes in the transfer function), enabling a further reduction of the overhead associated with recomputing photon maps. Unlike MC path tracing, photon mapping typically introduces some bias, often visible as low-frequency noise.…”
Section: Volumetric Photon Mapping Approachesmentioning
confidence: 99%
“…While this method allows real-time radiance reconstruction, the photon map should be regenerated every time the transfer function changes. To accelerate the photon map generation, Jönsson et al [24] identified photons invariant to changes of visual parameters (e.g., changes in the transfer function), enabling a further reduction of the overhead associated with recomputing photon maps. Unlike MC path tracing, photon mapping typically introduces some bias, often visible as low-frequency noise.…”
Section: Volumetric Photon Mapping Approachesmentioning
confidence: 99%
“…The presented methods have been integrated into an OpenCL-based path tracer in the Inviwo [10] visualization framework running on both the CPU and the GPU. The path tracer implementation utilizes partitioned tracking through a super-grid (8 3 voxels per grid cell) storing the extinction bounds and average of each grid cell, see [16] and [11] for more details. An Intel Xeon 2.5 GHz CPU with 32 GB random access memory and a Geforce 1070 GPU is uses as testing hardware.…”
Section: Real-world Examplesmentioning
confidence: 99%
“…[NEO*10] demonstrated a real‐time pipeline for analysing the 3D fMRI signal during the scanning process, using an approximated method for treating the fMRI signal as an emissive light source and fusing it with a co‐registered magnetic resonance imaging (MRI) scan [HLY07]. Later it has also been shown how to more accurately simulate this emissive light transport interactively in brain imaging data [JY17]. These methods, fusing fMRI and MRI data using light transport, form the basis for the 3D views in the herein presented work and we refer the reader to the multi‐modal medical visualization data survey by Lawonn et al .…”
Section: Related Workmentioning
confidence: 99%